Individual Differences in Audio-Vocal Speech Imitation Aptitude in Late Bilinguals: Functional Neuro-Imaging and Brain Morphology - Reiterer, Susanne M.; Hu, Xiaochen; Erb, Michael; Rota, Giuseppina; Nardo, Davide; Grodd, Wolfgang; Winkler, Susanne; Ackermann, Hermann (Frontiers in Psychology, 2011)
An unanswered question in adult language learning or late bi and multilingualism is why individuals show marked differences in their ability to imitate foreign accents. While recent research acknowledges that more adults than previously assumed can still acquire a “native” foreign accent, very little is known about the neuro-cognitive correlates of this special ability. We investigated 140 German-speaking individuals displaying varying degrees of “mimicking” capacity, based on natural language text, sentence, and word imitations either in their second language English or in Hindi and Tamil, languages they had never been exposed to. The large subject pool was strictly controlled for previous language experience prior to magnetic resonance imaging. The late-onset (around 10 years) bilinguals showed significant individual differences as to how they employed their left-hemisphere speech areas: higher hemodynamic activation in a distinct fronto-parietal network accompanied low ability, while high ability paralleled enhanced gray matter volume in these areas concomitant with decreased hemodynamic responses. Finally and unexpectedly, males were found to be more talented foreign speech mimics.